2000
DOI: 10.1212/wnl.54.8.1625
|View full text |Cite
|
Sign up to set email alerts
|

Functional MR evaluation of temporal and frontal language dominance compared with the Wada test

Abstract: There was a good congruence between hemispheric dominance for language as assessed with the Wada test and fMRI laterality indices in the frontal but not in the temporal lobes. The story listening and the covert sentence repetition tasks increased the sensitivity of detection of posterior language sites that may be useful for brain lesion surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
222
0
16

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(259 citation statements)
references
References 39 publications
20
222
0
16
Order By: Relevance
“…Reanalysing the study by Adcock et al (2003) shows that there are no differences in terms of LI values between pre-operative LTL and RTL patients when only patients with a lefthemispheric language dominance according to the IAP were selected. Because of the pre-operative language lateralization criterion and the almost perfect agreement between fMRI and IAP language lateralization reported in many studies (Binder et al, 1996;Yetkin et al, 1998;Lehéricy et al, 2000;Rutten et al, 2002a,b;Spreer et al, 2002;Adcock et al, 2003;Woermann et al, 2003) for RTL and LTL patients, the interhemispheric redistributions effects found in this study are more likely to occur due to the surgical intervention. Post-operative cerebral changes would moreover explain the rather large number of patients exhibiting disagreement between IAP and post-operative fMRI results as found in this study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Reanalysing the study by Adcock et al (2003) shows that there are no differences in terms of LI values between pre-operative LTL and RTL patients when only patients with a lefthemispheric language dominance according to the IAP were selected. Because of the pre-operative language lateralization criterion and the almost perfect agreement between fMRI and IAP language lateralization reported in many studies (Binder et al, 1996;Yetkin et al, 1998;Lehéricy et al, 2000;Rutten et al, 2002a,b;Spreer et al, 2002;Adcock et al, 2003;Woermann et al, 2003) for RTL and LTL patients, the interhemispheric redistributions effects found in this study are more likely to occur due to the surgical intervention. Post-operative cerebral changes would moreover explain the rather large number of patients exhibiting disagreement between IAP and post-operative fMRI results as found in this study.…”
Section: Discussionsupporting
confidence: 72%
“…Until now, extremely good correlations have been published between fMRI and the IAP, especially for epilepsy patients with a typical (i.e. left dominant) language representation (Binder et al, 1996;Yetkin et al, 1998;Lehéricy et al, 2000;Rutten et al, 2002a,b;Spreer et al, 2002;Adcock et al, 2003;Woermann et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most of this literature has focused on cerebral activations associated with semantic decisions, silent word generation, covert repetition, and covert naming in controls and patients with TLE (for a comprehensive review, see (45)). These studies have demonstrated prominent activations in left prefrontal areas (45,65-67), with less consistent activations in temporoparietal regions (65). Such data have led some experts to conclude that fMRI may be better suited for localizing expressive language areas within the frontal lobe than receptive language areas within temporal lobe regions ((68,69), but see (70,71)).…”
Section: Fmrimentioning
confidence: 99%
“…In recent years, several studies have compared fMRI and the IAP with respect to language lateralization, or evaluated the ability of fMRI to localize language functions in children and adults with epilepsy [12][13][14][15][16][17][18][19][20][21][22][23][24]. These and other authors used various language fMRI tasks including semantic decision [14,16,21,[25][26][27], verb generation/verbal fluency [13,19,20,23,[28][29][30], word generation [15,18,22,24], and sentence reading [17,31].…”
Section: Introductionmentioning
confidence: 99%
“…These and other authors used various language fMRI tasks including semantic decision [14,16,21,[25][26][27], verb generation/verbal fluency [13,19,20,23,[28][29][30], word generation [15,18,22,24], and sentence reading [17,31]. Some studies have also reported the use of more than one fMRI paradigm for language localization and lateralization [10,12,13,29,32,33], but the results of these studies have been mixed, with some tasks showing good and some poor correlation with the results of IAP.…”
Section: Introductionmentioning
confidence: 99%